The Impact of Problem-Based Learning on Students' Narrative Writing Proficiency in the Second Grade at SMAN 1 Pasir Penyu - agis, lidya; Novita, Loly; Wahyuningsih, Destri (ENJEL: English Journal of Education and Literature, 2025)
This study aims to determine problem based learning significantly an effect narrative text writing ability at second grade SMAN 1 Pasir Penyu. This research is included in quantitative research. The population in this study was class XI students, and the samples were class XI.6 as the control class and XI.2 as the experimental class. Data collection techniques are carried out using tests and documentation. The instrument in this research is a test of students’ narrative text writing ability. The research results found that the pre-test average for classes was X1.6 with in average of 42.08, while the pre-test average for class XI.2 was 45.55. With this, experimental classes and control classes can be determined based on the final results of the pre-test. Then, after the researchers used the treatment and gave a post-test as the experimental class (XI.2), the average results was 56.94, showing that the highest % of students’ writing ability classification was 55.6%. Thus, most of the students in the experimental class classified enough. While in the control class (XI.6) without treatment it was 46.66, showing that the highest % of students’ writing ability classification was 44.5%. Thus, most of students in the class are classified as enough. After analyzing the from both classes, an independent sample t-test was conducted to test the hypothesis. The Sig (2-tailed) value was less than significant level (0.000 < 0.05), so Ha was accepted. Based on the results of the research carried out, the problem based learning can be used as alternative solution in the teaching and learning process which is specialized in improving students’ writing ability. Students are trained to be active and collaborative to develop their writing ideas with friends and find story which that are expressed is the text.